Governance as a trialogue - Anthony R. Turton .....[et al.] (Berlin, 2007)
The Global Water Partnership notes that the crisis in the water sector is a one of governance. Water management is an integral part of ecosystem governance and is closely linked to the sustainable development discourse. This book unpacks the core elements of governance, with a specific focus on water. It analyzes the linkages between key variables in an effort to increase our understanding of what makes governance good.
Keywords: Water resource management